In VIVO Pengaruh Vitamin B-15 Dan Bekatul Organik Terhadap Penurunan Kadar Glukosa Darah - Yuniar Deddy Kurniawan; Puji Indriyani (AKPER Pasar Rebo, 2018)
Dibetetes mellitus is caused by eating habits with energy dense and low in fiber which causes an increase in blood glucose levels. Bran with high fiber content and rich in vitamin B 15 which is very useful in improving the body's metabolic work, the content of vitamin B15 which is high enough in bran can be used to reduce sugar levels and improve the body's metabolism in people with diabetes mellitus. The aim of this study was to find a therapeutic model with vitamin B 15 and organic bran to accelerate healing of people with diabetes mellitus by the in vivo method in white male rats. The research was conducted in 2 stages, namely, the first stage; examine the factors and parameters of the bran production process from sifting to the drying process. The experimental design of the stabilization process uses the Taguchi Method. Characterization of radiation is carried out on organic rice varieties, namely bagendite. Data analysis used ANOVA analysis to obtain the most dominant factors that influence bran yield / products to be tested for composition / chemistry. The second stage is to use rice bran as a therapeutic agent for diabetes millitus, which in the initial stages used in vivo with 3 groups of mice (each of which amounted to 6 animals) with blood sugar levels (> 120 mg / dL), experimental process temperatures will reduce protein levels contained in rice bran, protein content decreases with increasing temperature. Each time the sinking and oven were best at 10 with diabetic treatment, and were cured / treated with bran and vitamin B 15. The results of testing to obtain protein and fiber levels showed that the minutes were higher. Fiber content has the highest value, the right process parameter is 10 minutes, oven time is 10 minutes and temperature is 60 o C. Based on the ANOVA test it can be concluded that the treatment of bran and a mixture of bran and vitamin B15 in diabetic rats decreased blood glucose levels in rats compared to the control group on day 7, day 14 and day 15 (p <0.005). Based on the post hoc test, results were obtained between treatment groups not significantly lowering blood glucose levels in mice (P> 0.005)